2012
DOI: 10.1371/journal.pone.0039238
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Field-Effect Microdevice for Monitoring Membrane Transport in Xenopus laevis Oocytes via Lateral Proton Diffusion

Abstract: An integrated microdevice for measuring proton-dependent membrane activity at the surface of Xenopus laevis oocytes is presented. By establishing a stable contact between the oocyte vitelline membrane and an ion-sensitive field-effect (ISFET) sensor inside a microperfusion channel, changes in surface pH that are hypothesized to result from facilitated proton lateral diffusion along the membrane were detected. The solute diffusion barrier created between the sensor and the active membrane area allowed detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…This preference has also been confirmed by surface pH measurements on Xenopus oocytes using a pH-sensitive electrode (Ravera, Virkki et al 2007). For the electroneutral NaPi-IIc, the preference for HPO 4 2-is consistent with its 2:1 Na + :P i stoichiometry (Bacconi, Virkki et al 2005) and based on recent surface pH measurements using an ion-sensitive field effect transistor (ISFET) sensor (Schaffhauser, Patti et al 2012). …”
supporting
confidence: 77%
See 1 more Smart Citation
“…This preference has also been confirmed by surface pH measurements on Xenopus oocytes using a pH-sensitive electrode (Ravera, Virkki et al 2007). For the electroneutral NaPi-IIc, the preference for HPO 4 2-is consistent with its 2:1 Na + :P i stoichiometry (Bacconi, Virkki et al 2005) and based on recent surface pH measurements using an ion-sensitive field effect transistor (ISFET) sensor (Schaffhauser, Patti et al 2012). …”
supporting
confidence: 77%
“…SLC20 proteins show an apparent affinity constant for total P i (K 0.5 Pi ) typically <100 µM (pH 7.4, [Na + ] =100 mM) and they preferentially transport monovalent P i (H 2 PO 4 -) (Saliba, Martin et al 2006;Ravera, Virkki et al 2007). The P i species preference was established by combining electrophysiology and tracer flux assays as for the SLC34 isoforms (Ravera, Virkki et al 2007), and has also been confirmed by surface pH measurements on Xenopus oocytes (Ravera, Virkki et al 2007;Schaffhauser, Patti et al 2012). The preference for monovalent P i and relative insensitivity of transport kinetics to reduced pH means that SLC20 proteins could support P i transport under acidotic conditions, where SLC34 proteins are functionally compromised.…”
Section: Slc20mentioning
confidence: 84%
“…By culturing an oocyte (female Xenopus laevis frogs) on the gate of the ISFET, the kinetics of transporter-substrate interaction on the cell membrane can be monitored non-invasively in real time without labeling. Furthermore, we fabricated an integrated microdevice for measuring proton-dependent membrane activity at the surface of an oocyte [14]. These results indicated that local protons could be monitored with high spatiotemporal precision and reliability due to the much faster lateral diffusion of protons relative to other solutes along with the plasma membranes.…”
Section: Introductionmentioning
confidence: 94%
“…During these events, any observed changes in the channel conductivity can be correlated to polarity and density of charges at the gate, thus providing a basis for identification and quantification of these molecules. This strategy, often termed "bio-FETs", has been validated for a variety of targets [1][2][3][4] including ions [1], enzymes [5], proteins [6,7], nucleotides [8][9][10][11] carbohydrates [12,13] and even cells [14][15][16][17][18][19][20][21]. The beauty of bio-FETs may be highlighted in the fact that it represents a label-free determination platform, which can be readily downsized and integrated by virtue of today's advanced semiconductor fabrication technology.…”
Section: Introductionmentioning
confidence: 99%